Search for right-handed W bosons in top quark decay - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2005)
We present a measurement of the fraction f+ of right-handed W bosons produced in top quark decays, based on a candidate sample of tt̄ events in the lepton+jets decay mode. These data correspond to an integrated luminosity of 230pb-1, collected by the D0 detector at the Fermilab Tevatron pp̄ Collider at s=1.96TeV. We use a constrained fit to reconstruct the kinematics of the tt̄ and decay products, which allows for the measurement of the leptonic decay angle θ* for each event. By comparing the cos θ* distribution from the data with those for the expected background and signal for various values of f+, we find f+=0.00±0.13(stat) ±0.07(syst). This measurement is consistent with the standard model prediction of f+=3.6×10-4. © 2005 The American Physical Society.